2014 Update of the EULAR standardised operating procedures for EULAR-endorsed recommendations. Issue 1 (26th September 2014) - van der Heijde, Désirée; Aletaha, Daniel; Carmona, Loreto; Edwards, Christopher J; Kvien, Tore K; Kouloumas, Marios; Machado, Pedro; Oliver, Sue; de Wit, Maarten; Dougados, Maxime
Abstract : In this article, the European League Against Rheumatism (EULAR) standardised operating procedures for the elaboration, evaluation, dissemination and implementation of recommendations endorsed by the EULAR standing committees published in 2004 have been updated. The various steps from the application to implementation have been described in detail.